Pengaruh Kepemimpinan, Karakteristik Individu dan Disiplin Kerja Terhadap Kinerja Karyawan Anindo Multimedia - Zia'ul Huda, Elida; Perdana, Dian Noor Citra; Lestari, Sri Isfantin Puji; Triatmono, Agus (Sekolah Tinggi Ilmu Ekonomi Surakarta, 2023)
The purpose of this study was to determine the effect of leadership, individual characteristics and work discipline on the performance of Anindo Multimedia employees located in Sukoharjo City. This research is a primary data research using a questionnaire. The population is Anindo Multimedia Sukoharjo employees as many as 54 people. The sample is 54 respondents. Data analysis techniques using SPSS. The data analysis method uses: (1) Research instrument test, namely validity and reliability test, (2) Classical assumption test, namely multicollinearity test, autocorrelation, heteroscedasticity, normality. (3) Test the hypothesis, namely multiple linear regression test, t test, F test and R2 test. The results of the study show that leadership, individual characteristics and work discipline affect employee performance.